Pengembangan Media PowerPoint Interaktif Berbasis Inkuiri Terbimbing pada Materi Asam Basa Kelas XI SMA/MA - Romy Chania; Syamsi Aini (Universitas Negeri Padang, 2021)
ABSTRACT This study aims to develop interactive PowerPoint learning media based on guided inquiry on the acid-base topic and reveal the validity and practicality of the developed media. This research belongs to the type of research and development with 4-D development model (define, design, develop, disseminate). Limited to the develop stage. The instrument of this research is a questionnaire of validity test and practicality test. The subjects of the validity test of this interactive PowerPoint learning media were two chemistry department lecturers and three SMA chemistry teachers. The practicality test subjects of this interactive PowerPoint learning media were three SMA chemistry teachers and sixteen SMAN 1 Batang Kapas students. The data from the validity and practicality tests were analyzed using the Aiken's V formula and descriptive analysis methods. Based on the results of the analysis of the validity test data obtained a score of 0.87 with a valid category. And the results of the analysis of the practicality test data on teachers obtained a value of 90% and for students of 95.4% with a very high practicality category. Keywords:PowerPoint, Guided Inquiry, Acid-Base